Factors affecting carbon dioxide emissions embodied in trade - Jong Woo Kang; Joshua Anthony Gapay (Asian Development Bank (ADB), 2023)
Trade encourages economic expansion and improves welfare based on international division of labor. However, trade also has an environmental footprint, particularly in the form of carbon dioxide (CO2) and other emissions. This paper examines the impact of environmental regulation in exporter and importer economies on cross-border carbon flows. It uses pooled estimation, random effects, fixed effects, fixed effects with instrumental variables, and Poisson pseudomaximum likelihood models to estimate the effect of more stringent environmental regulation, while controlling for scale, technique, and composition effects associated with CO2 emissions. While stricter environmental regulations help reduce CO2 emissions from domestic production, leading to lower CO2 emissions embodied in exports, stricter regulations on the importing side lead to higher CO2 emissions embodied in imports. More importantly, stricter environmental regulations could encourage further outsourcing of intermediate inputs by exporters, prompting carbon leakages in the upstream segment of global value chains.
Keywords: F1; F14; F18; 330; CO2 emissions; carbon leakage; trade; global value chain